FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI ANGGOTA P3A DALAM PENGELOLAAN IRIGASI PADA WATER RESOURCES AND IRRIGATION SECTOR MANAGEMENT PROGRAM (WISMP) DI KECAMATAN KURANJI KOTAPADANG - Fira Yenifa; Idris Idris (Program Studi Magister Manajemen, 2013)
This Research is aimed to analyze the influence of a leadership, the managing of policy, education level and the benefit of irrigation sector toward P3A participation in irrigation of Water Resource and Irrigation Sector Managing Program or( WISMP). This Research is using a survey method with the analyze of descriptive of associative with the regreation of double program. The member of Respoundenceare about 187 people consist of P3A member of WISMP in Kuranji Regency. The example of this research is choosed by the Sampling of Random Method it based on strata identification for education from the member of P3A WISMP. The Result of the research conclude that leadership, managing policy and irrigation benefit, they are significant influenced to ward participation to P3A members in irrigation program in a WISMP Program. Its means with the development of leadership, managing policy and benefit of irrigation will increase of member participation of P3A in irrigation managing, meanwhile, level of education, not really signification influence toward member P3A participation in managing irrigation, although the education always improving. That way of the leadership, managing policy, education level and the benefit of irrigation have a positive effect to all of them. So with the conclusion we get the Leadership influence, policy management, education management and benefit of irrigation toward member of P3A participation in of WISMP only 45,50 % while 58,50% is again influenced by other variable. Keyword : Participation, Leadership, Policy of management, Education, Benefit Irrigation.